Kajian Etnologi Guna Menentukan Substansi Sosio-Kultural Sebagai Potensi Pengembangan Masyarakat Yang Kontekstual Kepada Suku Tugutil di Pulau Halmahera, Maluku Utara - Marde Christian Stenly Mawikere; Sudiria Hura (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article carries out a ethnology or cultural anthropological study of the Tugutil tribe on the island of Halmahera, North Maluku as one of the most isolated tribes in Indonesia. With this study, it will determine the socio-cultural substance or their cultural values ​​that become potential in the contextual development of society. The cultural anthropological approach in this study was carried out using the literature study method to obtain data and information on cultural components ranging from history or origins, distribution, settlement patterns, economic cycles, inculturation of social groups and individual life cycles of the Tugutil tribe. Through this research, the socio-cultural substance or cultural values ​​of the Tugutil tribe that contribute to contextual human development efforts are determined. Thus, it can be concluded that contextual community development efforts must pay attention and give meaning to the context of the ecosystem, economy, and ecology of the Tugutil tribe who are familiar with forests, soil and water as their source of life. Keywords: Culture, Locality, Values, Empowerment, Contextual.